Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597078
|View full text |Cite
|
Sign up to set email alerts
|

Towards building a universal defect prediction model

Abstract: To predict files with defects, a suitable prediction model must be built for a software project from either itself (withinproject) or other projects (cross-project). A universal defect prediction model that is built from the entire set of diverse projects would relieve the need for building models for an individual project. A universal model could also be interpreted as a basic relationship between software metrics and defects. However, the variations in the distribution of predictors pose a formidable obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 41 publications
1
65
0
6
Order By: Relevance
“…For example, Turhan et al [26] applied a nearest neighbor filtering technique to filter out those irrelevant project data in the setting of CPDP, leading to a better prediction performance. More discusses on the comparison between WPDP and CPDP please refer to [4,10,27,28]. Unfortunately, very few prior studies paid attention to the issue in question in CPDP settings.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Turhan et al [26] applied a nearest neighbor filtering technique to filter out those irrelevant project data in the setting of CPDP, leading to a better prediction performance. More discusses on the comparison between WPDP and CPDP please refer to [4,10,27,28]. Unfortunately, very few prior studies paid attention to the issue in question in CPDP settings.…”
Section: Related Workmentioning
confidence: 99%
“…So, we should take into consideration various factors (rather than just accuracy) when applying them to different types of actual projects with limited resources, which is required to make an optimal (or near-optimal) tradeoff among generality, performance and construction cost. That is, we want to find one or more appropriate regression models that can be used in different scenarios, because the previous studies about defect-proneness prediction have showed that the classifiers which are simple and easy to use tend to perform well in both within-and cross-project scenarios [10,27]. In particular, is this still practicable for defect numbers prediction?…”
Section: Research Questionsmentioning
confidence: 99%
“…• Remove code comments that contain any of the commonly used terms in defect prediction [20]. bug, fix, error, issue, crash, problem, fail, defect, patch …”
Section: Comment Selectionmentioning
confidence: 99%
“…In the area of defect prediction for quality improvement, Peters et al [5] introduce guidelines to be used in the building of software quality predictors in case of scarcity of data while D'Ambros et al present a comparison between the different prediction approaches [6]. Zhang et al Platform to obtain an objective value of the software development process quality present in [7] a study for the specification of a universal defect predictor. Gamalielsson et al [8] define the health of an open source ecosystem as an important decision factor when considering the adoption of an OSS component.…”
Section: Table 1: European Projects Focusing On Oss Data Analysismentioning
confidence: 99%